2018
DOI: 10.1002/pd.5204
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between preoperative fetal head circumference and 2‐year cognitive performance after laser surgery for twin‐twin transfusion syndrome

Abstract: Smaller preoperative HC percentiles identified children at risk of lower, but still within normal range, total BDI-2 scores. The discordance in HC percentiles between the donor and recipient twin decreased after laser surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In particular, neurological outcomes were not assessed in this study. We have previously found that preoperative head circumference percentiles were associated with overall cognitive performance at 2 years of age [39]. Smaller preoperative head circumference identified children at risk of lower but still within normal range cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, neurological outcomes were not assessed in this study. We have previously found that preoperative head circumference percentiles were associated with overall cognitive performance at 2 years of age [39]. Smaller preoperative head circumference identified children at risk of lower but still within normal range cognitive performance.…”
Section: Discussionmentioning
confidence: 99%